Makna, Urgensi, Historis, serta Perbedaannya dengan Qowaid Fiqhiya dan Qowaid Tasri’iyah - Gazali, Muh. Rakasiwi A.; F, Fatmawati; Amin, Abd. Rauf Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of Islamic law in the modern era requires a methodology of istinbāṭ capable of addressing contemporary issues. However, in practice, confusion still arises in understanding the differences in function between Qawāʿid Uṣūliyyah, Qawāʿid Fiqhiyyah, and Qawāʿid Tasyriʿiyyah. This reality raises a fundamental question regarding the conceptual and applicative positions of these three types of legal maxims in the determination of Islamic law. This study formulates the following research problems: how do the functions and applications of Qawāʿid Uṣūliyyah, Qawāʿid Fiqhiyyah, and Qawāʿid Tasyriʿiyyah differ, and how can their integration strengthen contemporary Islamic legal methodology. This research employs a normative-qualitative method with a descriptive-comparative approach. Data were collected from classical uṣūl al-fiqh literature, fiqh works, and contemporary studies (2018–2025), and were analyzed using content analysis to identify differences, similarities, and patterns of integration among the three types of legal maxims. The findings indicate that Qawāʿid Uṣūliyyah function as the methodological foundation in the process of legal istinbāṭ, Qawāʿid Fiqhiyyah serve as practical guidelines for resolving everyday cases, while Qawāʿid Tasyriʿiyyah function as a normative basis for the formulation of Islamic law oriented toward maqāṣid al-sharīʿah..